2010
DOI: 10.1002/eji.201040575
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic immunological synapse mediates homeostatic TCR‐dependent and ‐independent signaling

Abstract: For homeostasis, T cells integrate non-cognate TCR-dependent and -independent signals to survive and weakly proliferate. In contrast to antigen-specific, stable, and long-lived contacts, signaling in short-lived homeostatic interactions depends upon the coordination of ongoing T-cell migration on the surface of DC and signaling at the cell-cell junction.To mimic peripheral tissues and analyze how T-cell migration and cell-cell signaling are integrated, we used live-cell imaging and 3-D reconstruction of fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Instead, at the contact with APC, WASP‐deficient CD4 + T cells displayed an abnormally sustained migrating morphology characterized by an active leading edge and an elongated uropod. It has been shown that DC‐mediated T‐cell survival is dependent on cell‐to‐cell contact and that it may be driven by signalling originating from the uropod . It would therefore be interesting to test whether the elongated uropod observed in WASP‐deficient T cells contributes to their high propensity to survive at the contact with iDC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, at the contact with APC, WASP‐deficient CD4 + T cells displayed an abnormally sustained migrating morphology characterized by an active leading edge and an elongated uropod. It has been shown that DC‐mediated T‐cell survival is dependent on cell‐to‐cell contact and that it may be driven by signalling originating from the uropod . It would therefore be interesting to test whether the elongated uropod observed in WASP‐deficient T cells contributes to their high propensity to survive at the contact with iDC.…”
Section: Discussionmentioning
confidence: 99%
“…However, WASP deficiency resulted in a loose confinement of high‐affinity LFA‐1 to the mid‐cell focal zone and a dispersion towards the uropod. During T‐cell scanning of DC surfaces, LFA‐1 is dynamically redistributed from the leading edge to the mid‐cell zone where it forms a signalling platform . WASP deficiency might therefore affect the spatial organization of LFA‐1 signalling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spread of virus between infected and susceptible target cells can take place via several pathways, including: release of cell-free virus particles which are then stochastically encountered by a target cell; sequestration of virus particles by dendritic cells and subsequent delivery of these particles to a target cell (a process termed trans -infection [ 1 ]); and the process of cell-to-cell transmission, whereby an infected cell directly interacts with a target cell, thus forming a transient adhesion structure known as the virological synapse (VS; [ 2 , 3 ]), which facilitates transfer of newly released viral particles. Such interactions are thought to occur most frequently in secondary lymphoid tissue, such as in lymph nodes and the gut-associated lymphoid tissue (GALT), where high cell density and migratory scanning behavior of T cells, facilitated by the architecture of the stromal environment, provide conditions conducive to controlled cell–cell interactions, including antigen presentation through the immunological synapse [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%